How does TikTok Shop Live Streaming Advertising Influence their Consumers' Purchase Intention? - Ng Yee Xin; Zing Ying Ngieng; Noor Anis Batrisya; Noor Shahdeena; Muhammad Azriel; Muhammad Rezandi; Kadek Ayu Silvi Septya Dewi; Ramadisto Raez Naqvi (Advances in Global Economics and Business Journal, 2023)
With the progress of time, the use of online shopping platforms has increased tremendously in these years, especially during the Covid-19 pandemic. Live streaming advertising functionality is one of the most powerful marketing tools provided by e-commerce platforms to allow sellers to promote their products and services to e-commerce users through live streaming. As one of the most popular e-commerce platforms in Indonesia and as a rising e-commerce star in Malaysia, TikTok Shop has successfully used live-streaming advertising methods to increase its sales. This study was conducted to investigate the factors that influence consumers' purchase intentions in using live-streaming advertising methods through the TikTok Shop. Primary data and secondary data were needed for this project. A digital questionnaire is created and distributed to 200 respondents to collect data from them as the primary data for this paper. The findings demonstrated that TikTok influencer, interactivity, service quality, sales promotion for branded product, convenient, credibility and addiction influenced the purchase intention of TikTok users. Recommendations and implications were conveyed.